Análisis multivariado de la variación reflectométrica durante el proceso de crecimiento (2001)
ABSTRACT: Skin colour through reflectometry was studied in a school sample of 1,682 children of both sexes (889 girls and 793 boys) from the Biscay province (Basque Country) with a range of ages from 8 to 19 years. A EEL DS29 digital Unigalvo reflectance spectrophotometer was used, by measuring on the forehead and inner arm with 601 to 609 filters. The information got by measuring with the 9 filters (18 variables) was finally recorded in the reflectance measures done with the odd filters (601, 603, 605, 607 and 609), to which filter 604 was added. Ontogenetic variations and sexual dimorphism were studied at a multivariate level by using a Principal Component Analysis (PCA) for these variables. After the rotated solution of the PCA two factors of size (arm and forehead) were obtained. In general, a fair lightening of the skin colour in the arm with the age in both sexes was observed, statistically significant for some groups of age, and a decrease of the percentage of reflectance at the forehead darkening. Sexual dimorphism for skin colour was remarkable during puberal and postpuberal periods, but was attenuated at the end of the considered ontogenic period. General tendency indicated that girls tended to be less coloured than boys. Female sexual maturation could be considered as a lightening factors in some non-exposed areas.